Online teaching in China during the COVID-19 pandemic - Li Yuebo; Siti Hajar Halili; Rafiza Abdul Razak (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study was undertaken to understand the overall impact of China's online education practices at all levels during the COVID-19 pandemic. A study of remote learning was an opportunity to better understand the long-term impact and adoption of structural and pedagogical practices in the post- pandemic period. The main research subjects were teachers and administrators in K-12 primary, vocational colleges and universities. The adult learning andragogy model was utilized as a framework for understanding the conditions under which students and faculty learned and taught in a remote learning environment. Statistical analysis of survey data indicated the research subjects had expectations for a change in teaching methods into the future. Future research is needed to carry out an in-depth analysis of how to build a model for online education. As a result of this study, it was determined that the continuous evaluation of online education would help in shaping best practice for teaching and learning in a remote environment within China’s educational system.